Democratization of public transportation since 1820 - Andolf, Göran (University of Gothenburg, 2013)
The study deals with the variations of caravan traffic, i.e. the number of departed horses per year in the whole country and in various counties (1855-1906) and in tax charge districts and at single inns (about 1820-1920). Furthermore the variations in sea passenger traffic, i.e. yearly incomes for 66 passenger vessels in domestic traffic during the period of 1860 to 1920. Above this there is information on opening and closing hours per year of Göta Kanal and Trollhätte Kanal and the person kilometers of the railways.

Undersökningen tar upp skjutstrafikens variationer, dvs antalet utgångna hästar per år i hela riket och i olika län (1855-1906) samt i fögderier och vid enskilda gästgivargårdar (omkr. 1820-1920). Dessutom behandlas fartygspassagerartrafikens variationer, dvs årliga inkomster för 66 passagerarfartyg i inrikes trafik under perioden 1860-1920. Därutöver finns uppgifter om Göta kanals och Trollhätte kanals öppethållande per år samt järnvägarnas antal personkilometer. Insamlingen har skett med hjälp av regional statistik.
Resandets demokratisering efter 1820
Keywords: freight transport; godstransport; road transport; vägtransport; sea transport; sjötransport; railway transport; järnvägstransport; public transport; kollektivtrafik; passengers; passagerare; canals; kanaler; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; HISTORY; HISTORIA; Transport Systems and Logistics; Transportteknik och logistik; History; Historia